Finance as an (Ever More Fragile) ‘Perpetual Mania’: Have They All Lost Their Collective Minds? - Palma-Penco, J (Oxford University Press, 2022)
This paper analyses events in financial markets since the 2008 financial crisis in both the developed and the developing worlds, giving especial attention to the processes of ‘financialisation’. Its main conclusion is that we are paying the price (a huge one) for two related phenomena. The first relates to the failure of economic theory since the 1970s, especially (although not only) of the mainstream type, to really take on board those developments in the world of international finance that ‘did not fit in their models’ (such as the 1970s stagflation; Volker’s subsequent radical monetarist recession; the ‘savings and loan’ debacle following Reagan’s financial liberalisation and deregulation-policies reinforced in the 1990s; the inability of both monetarists, and traditional Keynesian policies to revert Japan’s ‘lost decade’; and the ‘endogenous’ nature of the 2008 financial crisis). Basically, economic theory has failed to reinvent itself when needed as it did after the 1930s crash. The second, in turn, relates to the fact that rocketing the net worth of a few individuals was a rather odd way to reactivate fragile economies after the 2008 crisis and the 2020 pandemic. But when rentier agents were allowed to become ‘too-large-to-be-challenged’, it was likely that these newly (and artificially) created ‘whales’ would capture policy-making and take it in this direction-leaving the politicians and central bankers to tell stories explaining why the very rich should become the biggest welfare recipients of all time. As one group of Native Americans used to say, ‘Those who are better at storytelling will dominate the world’. © The Author(s) 2022.